Pengaruh Kepuasan Kerja Terhadap Komitmen Karyawan Rumah Sakit Mata Undaan Surabaya - Intan Ayu Ningkiswari; Ratna Dwi Wulandari (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2017)
Preliminary survey result showed the number of employees knowledge about the event held by Undaan Eye Hospital in Surabaya reached 52,8%. It means more than 20% employees are not aware of activity outside the work which that number can affect to decreasing employee commitment to the organization. Job satisfaction factors divided into 5 there are pay satisfaction, promotion, coworker, supervisor and the job characteristic. The aim of this study is to analyze the influence job satisfaction to employee commitment. Observational analytic was used in this research with the cross sectional design. The data was obtained through questionnaire with simple random sampling involving 62 employees as the sample of this research. The data obtained were analyzed using logistic regression test univariate (α=0,05) to examine the influence of Job satisfaction to employee commitment. The test result indicates that job satisfaction significantly influenced employee commitment at significance value of 0,02. Job satisfaction factors that there are influences toward employee commitment are employee’s pay satisfaction (sig=0,001), promotion (sig=0,005), supervisor (sig=0,004) and job characteristic (sig=0,001). On the other hand, the employee’s coworker satisfaction does not influence the employee commitment.Keywords: employee commitment, job satisfaction, job satisfaction factors.